2023
DOI: 10.1186/s40798-023-00610-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Physical, Physiological, Nutritional and Anthropometric Profiles of Soccer Referees

Abstract: Background The importance of soccer referees is widely accepted by international soccer organizations and governing bodies, although there is little research summarizing and appraising the literature on soccer referees. The aim of this study was to systematically review the information related to physical demands, nutrition and physiological profiling of soccer referees. Methods Conforming with Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Main referees and assistant referees play pivotal roles in football matches and are responsible for interpreting and judging various occurrences on the field. Like players, referees must have adequate levels of physical fitness to effectively fulfil their duties during the game [1][2][3][4]. Previous studies [4][5][6] have examined the development of physical capacities and their impact on the performance of football referees, indicating that higher levels of cardiorespiratory capacity lead to improved referee performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main referees and assistant referees play pivotal roles in football matches and are responsible for interpreting and judging various occurrences on the field. Like players, referees must have adequate levels of physical fitness to effectively fulfil their duties during the game [1][2][3][4]. Previous studies [4][5][6] have examined the development of physical capacities and their impact on the performance of football referees, indicating that higher levels of cardiorespiratory capacity lead to improved referee performance.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review has found that factors such as age are not good discriminators of performance for referees [4], as older referees kept the same distance to the ball despite covering a shorter distance. Experience may play an important role in making older referees more efficient in their movement, eventually compensating for fewer intense actions and a shorter distance covered with better positioning.…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to maintain the standard of the competition, it is imperative that referees consistently maintain their physical fitness and enhance their psychological and technical-tactical proficiencies. 2 Moreover, in various sports, 3 including basketball, the judgment of the referee is impacted by the ideal position, which is ascertained through physical motion on the court. 4 The physical performance of basketball referees has garnered scientific interest as a means to enhance the overall quality of the basketball game.…”
mentioning
confidence: 99%